Epidemiology of canine mammary gland tumours in Espírito Santo, Brazil - do Carmo Silva, Halana; de Oliveira, Ayisa Rodrigues; dos Santos Horta, Rodrigo; Rassele Merísio, Alice Corrêa; de Sena, Bruna Voltolin [UNESP]; Carlos de Souza, Mayara Coutinho; Flecher, Mayra Cunha (Universidade Federal do Rio Grande do Sul, 2019)
Background: Mammary tumours represent about 50 to 70% of all neoplasms in female dogs and their occurrence is directly related to the reproductive status and patient´s age. The purpose of this research was to apply the Brazilian consensus on diagnosis, prognosis and treatment of canine mammary tumours and to define the regional epidemiological aspects of canine mammary gland tumours in Vitoria metropolitan region (ES, Brazil) between 2012 and 2016 and to correlate the macroscopic characteristics such as lesion size and location of the neoplasm with histopathological diagnosis, tumours grade and lymph node metastasis. Materials, Methods & Results: Data were collected from the archives of the Laboratory of Animal Pathology of UVV and medical records of patients attended at the Veterinary Hospital Prof. Ricardo Alexandre Hippler in 5 years (2012 to 2016). The animals were separated into groups by age to facilitate classification in the group with the highest occurrence of neoplasms. The evaluation of the macroscopic characteristics was performed through the histopathological record described in the pathology laboratory, for each patient, at the time of the initial evaluation. After descriptive analysis, data was correlated using Spearmann test, and frequency dispersion was evaluated using chi-square test, both in the software Graph Pad Prism v. 6.01. This study included 255 bitches and diagnosis of 486 lesions, once 48.6% of the dogs had more than one lesion, classified according to the Brazilian Consensus for Canine Mammary Tumours and graded according to Elston and Ellis system. 86.8% of lesions were consistent with actual mammary neoplasms, of which 67% were malignant and 20% were benign. Non-neoplastic lesions corresponded to 7.2% of cases and 5.8% were extra-mammary neoplasms, with an increased incidence of lipomas (39.3%) and mast cell tumours (32.1%). Cross-breed dogs represented 26.7% of cases. Poodles (25.5%), Pinschers (9.8%) and Dachshund (4.7%) were overrepresented. Among mammary glands, inguinal and caudal abdominal were the most affected with 30.8% and 25.4%, respectively. Regarding the histopathological grade, 43.7% of the malignant mammary gland tumours were grade I, 40% grade II and 16.2% grade III. The neoplasms smaller than 3 cm in diameter, corresponded to 43.7% malignant neoplasms, of which 75 corresponded to grade I. Those larger or equal to 3-5 cm in diameter corresponded to 22.1% malignant neoplasm, of which 31 corresponded to grade II, and those larger than 5 cm in diameter corresponded to 25.8% malignant neoplasms, of which 34 corresponded to grade II. Macroscopic ulceration was reported in 35/486 neoplasms; of these, 85.7% were malignant. Microscopically necrosis was evidenced in 11.7% of malignant neoplasms and there was a weak, positive correlation between the occurrence of necrosis and ulceration (P < 0.0001; rs = 0.223), which was also correlated with tumour size and histological grade. Of these patients, 24.4% had metastases, and of these, 8.8% presented macroscopic abnormalities in the lymph node. Discussion: Older dogs are at higher risk of developing malignant mammary gland tumour when compared to young bitches, most neoplasms with a histopathological grade III occurred in animals older than 10 years, in agreement with the literature. Age increasing might be related to more biologically aggressive mammary gland tumours. Early neutering is commonly recommended to prevent proliferative abnormalities in the mammary glands, but it has been related to several disorders, and neoplasms, in some breeds. Multiple tumours in more than one mammary gland with different histopathological diagnoses among them, isn’t related to multicentric disease or worse prognosis, as also seen in this survey. Among mammary glands, the inguinal and caudal abdominal are often the most affected, as it was observed in this study; however, no differences were observed in the occurrence of malignant neoplasms, benign or non-neoplastic.
Keywords: Breast cancer; Dogs; Histopathology; Oncology